Modelagem do sequenciamento no processo de lingotamento contínuo por métodos exatos e heurísticos - Allan Messeder Caldas Bretas (2013)
This dissertation approaches the production scheduling problem in the Continuous Casting sector of a Brazilian steel company. The objective function of the problem works the trade-off between the mix cost and the setup cost. One of these two options must be chosen between any two jobs in subsequent positions on sequencing, and the affinities between the steel types determine the mixing cost. Two mathematical models are developed to solve the problem, which present good results on small instances. Furthermore, an algorithm is developed using Iterated Local Serach (ILS) metaheuristic as a strategy for solving large instances. Actual instances are provided and allow the comparison of the methods to the solution presented by the company.